Radical innovation in (multi)family owned firms - Chirico, Francesco; Duane Ireland, R.; Pittino, Daniel; Sanchez-Famoso, Valeriano (Journal of Business Venturing, 2022)
By integrating organizational learning theory with the family firm literature, we seek to enhance our understanding of radical innovation in (multi)family-owned firms. We theorize that the goal diversity and path dependency that multifamily ownership creates negatively affects the positive relationship between knowledge integration and radical innovation. However, this is not the case for multifamily-owned firms in which family members embrace a commitment to change. We contend that commitment to change mitigates the negative moderating effect of multifamily ownership by ensuring the effective translation of integrated knowledge into radical innovation within the firm. Overall, our results highlight the complexity of radical innovation in (multi)family-owned firms as a product of the joint effect of knowledge integration, the number of unrelated owning families, and a commitment to change.